Trade policy as an exogenous shock: Focusing on the specifics - Andrew Greenland; John W. Lopresti (W.E. Upjohn Institute for Employment Research, 2021)
This paper proposes a novel strategy for identifying the effects of import competition on economic outcomes that avoids standard concerns related to the endogeneity of trade policy and provides a consistent measure of exposure to trade over time. Conditioning on the level of import tariffs, our approach exploits cross-industry differences in the relative importance of specific rather than ad valorem tariffs. As they are expressed in per unit terms rather than as a share of value, the effective protection provided by a given specific tariff varies with price levels. Using digitized tariff line data between 1900 and 1940, we relate inflation-driven changes in trade protection to changes in imports and labor market outcomes in the full count U.S. census. We show that our measure predicts import growth at both the industry and county level. Using our measure as an instrument, we show that import competition reduces labor force participation in traded sectors during this period. Labor market effects are widespread but fall most heavily on those with little experience or fewer outside labor market options: the young, seniors, and those in rural areas.
Keywords: F1; F6; N1; N7; J2; 330; International Trade; Economic History; Trade Policy; Inflation; Labor Markets